Early provision of maternal colostrum by the oropharyngeal route to preterm infants - Nasuf, Amna Widad Ahmed (2019)
Preterm infants are those born before 37 completed weeks of gestation. Worldwide, about one million children die each year due to complications of prematurity and survivors may face lifelong disabilities. Approximately 50% of neonatal deaths and 17% of deaths among children under five are affected by prematurity. Colostrum is the first milk produced by the mother within the early few days after birth. Colostrum is very rich in immunological and growth factors that indicates its primary functions are protective and trophic. Oropharyngeal administration of colostrum (OPC) is a novel route that involves coating the infant’s oropharynx with a small amount of colostrum (0.1 to 0.5 ml) during the early neonatal period. Immune and growth factors in colostrum might interact with the oropharyngeal mucosal-associated lymphoid tissues to modulate the infant’s immune system and promote intestinal growth, potentially reducing infection and necrotising enterocolitis (NEC), improving survival and health outcomes. Ultimately OPC could provide a potential target to prevent mortality and morbidities of preterm and sick infants. This thesis aimed to investigate whether OPC administration during the early neonatal period prevents deaths, improves health outcomes and promotes the growth of preterm infants.